2021
DOI: 10.3389/fcell.2021.628330
|View full text |Cite
|
Sign up to set email alerts
|

The P2X7 Receptor in Osteoarthritis

Abstract: Osteoarthritis (OA) is the most common joint disease. With the increasing aging population, the associated socio-economic costs are also increasing. Analgesia and surgery are the primary treatment options in late-stage OA, with drug treatment only possible in early prevention to improve patients’ quality of life. The most important structural component of the joint is cartilage, consisting solely of chondrocytes. Instability in chondrocyte balance results in phenotypic changes and cell death. Therefore, cartil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 240 publications
2
20
0
Order By: Relevance
“…Osteoarthritis (OA) is an age-related degenerative joint disease that is characterized by the loss of articular cartilage, synovitis, subchondral bone sclerosis and osteophyte formation (1). With the intensification of population ageing, the incidence of OA has increased from 29.2 to 40.5/1,000 person-years between 1992 and 2013 (2), and OA seriously endangers the health of elderly people (3).…”
Section: Introductionmentioning
confidence: 99%
“…Osteoarthritis (OA) is an age-related degenerative joint disease that is characterized by the loss of articular cartilage, synovitis, subchondral bone sclerosis and osteophyte formation (1). With the intensification of population ageing, the incidence of OA has increased from 29.2 to 40.5/1,000 person-years between 1992 and 2013 (2), and OA seriously endangers the health of elderly people (3).…”
Section: Introductionmentioning
confidence: 99%
“…P2X7 is a key molecule involved in the regulation of inflammation, as well as other numerous cellular responses dependent on the type and level of stimulation. For example, over-activation of P2X7 induces damage or apoptosis (Li et al, 2021a). We observed that moderateintensity exercise did not affect the expression levels of P2X7 in healthy rats, while the expression level of P2X7 gradually increased with time in the ACLT-induced OA rats.…”
Section: Discussionmentioning
confidence: 56%
“…We previously reported that moderate-intensity exercise effectively alleviated cartilage loss and OA symptoms (Zhang et al, 2019). We also found that purinergic receptor P2X ligand gated ion channel 7 (P2X7) was involved in OA incidence and development (Li et al, 2021b); furthermore, its expression levels were closely related to biomechanical stress (Li et al, 2021a). However, it is still not known whether moderate-intensity exercises affect OA via the regulation of P2X7 expression.…”
Section: Introductionmentioning
confidence: 99%
“…P2X7R mediates Na and Ca influx and K efflux, and is involved in a variety of inflammatory responses and different mechanisms of cell death ( Surprenant et al, 1996 ; Bartlett et al, 2014 ). P2X7R participates in NLRP3 and caspase-11 distinct pathway-mediated pyroptosis and produces cartilage degrading enzymes to activate inflammatory factors in synovial tissue ( Haseeb and Haqqi, 2013 ; Viganò and Mortellaro, 2013 ; Li et al, 2021a ). Activated P2X7 promotes extracellular matrix degradation and pyroptotic inflammation in OA chondrocytes through NF-κB/NLRP3 crosstalk to aggravate the symptoms of OA ( Li et al, 2021b ).…”
Section: Introductionmentioning
confidence: 99%